К проблеме оптимизации принципов таксономического исследования языков - Сирота, Елена; Мигирина, Нина (Studia Rossica Posnaniensia, 2015)
This article deals with the problem of optimizing the principles of the taxonomic study of languages based on a method that “goes” from a category to its representation signs. The revealing of invariant and relevant categories, and the contrastive study of all the means of their linguistic representation in a number of Nostratic languages, allows us to provide an adequate, complete and exhaustive description of these categories by way of taxonomy. The article emphasizes that this approach to the contrastive description of languages is oriented toward the ethno-linguistic and axiological aspects of linguistics. The representation of a continuum in a language system associated with any ethos depends on the national psychology as well as ethnic mentality of language speakers and is implemented within the axiological paradigms of a given society. The author formulates the hypothesis that the comparative study of languages based on the principles of representative grammar is important both theoretically and practically as the set of basic categories of a continuum representation is common to all language systems.